Aid for trade making it effective. - Organisation for Economic Co-operation and Development (Paris OECD, 2006)
This book sets out how much aid OECD countries are already providing towards trade-related activities in developing countries and reviews the effectiveness of existing programs. It argues that reinforcing mutual accountability at the local level, together with a global review mechanism, would enhance the impact of Aid for Trade.--Publisher's description.
The origins -- The scope of the aid for trade agenda -- Donor support -- The global aid context : the challenges of scaling-up -- When is aid effective? -- Priorities for improvement -- An effective aid for trade partnership : local accountability and global review.
Keywords: Finance -- Developing countries; Poverty -- International cooperation; Developing countries -- Commercial policy